Xerosis: from pathogenesis to solving practical problems - Irina E. Torshina (Vestnik Dermatologii i Venerologii)
Xerosis is a widespread symptom of dermatoses of various etiologies and pathogenetic mechanisms, which is recorded in people of different ages with a wide range of frequency and severity. The article contains the most current data on the features of the development and clinical manifestations of xerosis in terms of its connection with various factors of endo- and exogenous nature. An analysis of modern publications devoted to the study of the mechanisms of xerosis formation depending on genetic and premorbid factors, the influence of external causes associated with the characteristics of skin care in healthy individuals, patients with endocrinopathies, infectious and non-infectious diseases, visceropathy and iatrogenics is presented. Regardless of the origin of xerosis, it is justified to include in basic therapy topical preparations of the Lipobase line based on colloidal oats in combination with auxiliary components, the systematic use of which makes it possible to relieve the symptoms of xerosis and improve the quality of patient’s life.